Crack as Proxy: Aggressive Federal Drug Prosecutions and the Production of Black–White Racial Inequality. Issue 3 (3rd October 2018) - Lynch, Mona; Omori, Marisa
Abstract : In this article, we empirically examine jurisdictional variations in federal crack prosecutions to measure whether aggressive crack prosecutorial practices are associated with racial inequality in federal caseload characteristics and outcomes. Building on theories that address the production of inequality in institutional settings, we hypothesize that U.S. Attorneys' offices that are more proactive in charging defendants with crack, relative to other kinds of drugs, and relative to case strength and seriousness, will demonstrate higher rates of black–white racial inequality in case outcomes across the entire criminal caseload. Consistent with theories of institutional racism, our findings demonstrate that aggressive crack prosecutions at the district level are a strong predictor of black–white inequality in conviction rates across the entire criminal caseload, and a much more modest predictor of inequality in final sentence outcomes. We conclude by discussing the importance of organizational‐level empirical analyses for more effectively uncovering the conditions under which inequality can and does flourish in legal settings, and suggest possible future lines of inquiry along these lines.